2002
DOI: 10.2205/2002es000080
|View full text |Cite
|
Sign up to set email alerts
|

Petrology of the Europe-Largest Burakovka early Paleoproterozoic layered pluton (Southern Karelia, Russia)

Abstract: The Burakovka layered pluton of basic and mafic rocks is the largest intrusive massif in the Baltic Province composed of Si-and Mg-rich boninite-like rocks. The pluton consists of two individual bodies, each having its own internal structure, and contacting each other in their apical parts, known as the Aganozero and Shalozero-Burakovka bodies. Both bodies have a similar rock sequence including five differentiated zones (upward): mafic rocks, pyroxenite, gabbro norite, pigeonite gabbro norite, and magnetite ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…It is a product of high temperature differentiation and crystallization of a magmatic pluton. This pluton was a long lived magma chamber that developed above a local mantle plume whose origin is associated with the activity of the megaplume responsible for the formation of Baltic shield province (Chistiakov et al, 2002). The age of the pluton is 2.42 to 2.44 Ga estimated from Sm-Nd and U-Pb methods (Koptev-Dvornikov et al, 2000).…”
Section: Sample Descriptionmentioning
confidence: 99%
“…It is a product of high temperature differentiation and crystallization of a magmatic pluton. This pluton was a long lived magma chamber that developed above a local mantle plume whose origin is associated with the activity of the megaplume responsible for the formation of Baltic shield province (Chistiakov et al, 2002). The age of the pluton is 2.42 to 2.44 Ga estimated from Sm-Nd and U-Pb methods (Koptev-Dvornikov et al, 2000).…”
Section: Sample Descriptionmentioning
confidence: 99%
“…It was believed earlier that large layered massifs had originated as a result of the one-act intrusion of huge magma volumes into the crust. However, our detailed geological, petrological, geochemical, and isotope-geochronological studies of the Burakovka and Monchegorsk layered plutons [Chistyakov et al, 2002;Sharkov et al, 2002], as well as of other layered rock complexes in the Kola and Karelia regions, revealed that all of them had been formed by the multiple replenishment of individual portions of fresh magma into the solidifying intrusive chambers. (If?).…”
Section: Formation Of Large Layered Intrusionsmentioning
confidence: 91%
“…For instance, the Burakovka Complex mentioned above consists of two intrusive bodies of different ages, Aganozero and Shalozero-Burakovka, which contact each other in their tops. The Aganozero body is approximately 50 million years younger than the Burakovka-Shalozero one, the age of the former being 2.37 Ga, and that of the latter, 2.43 Ga. Because these bodies were described in detail earlier [Chistyakov et al, 2002], their description is omitted here.…”
Section: Layered Intrusive Rocks Of the Cratonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Aganozero Block was then uplifted and eroded [33,34]. According to the other hypthesis, the blocks originally formed as independent chambers with their upper portions touching each other [32,35,36]. There is no well-defined boundary between the Burakov-Shalozero and Aganozero Blocks on a map of magnetic field anomalies (Figure 4b).…”
Section: Intrusionmentioning
confidence: 99%